1996
DOI: 10.1073/pnas.93.24.13797
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome-dependent endoplasmic reticulum-associated protein degradation: An unconventional route to a familiar fate

Abstract: Until recently, the degradation of aberrant and unassembled proteins retained in the endoplasmic reticulum (ER) was thought to involve unidentified ER-localized proteases. We now show that the ER-associated degradation (ERAD) of two mutant proteins that accumulate in the ER lumen is inhibited in a proteasome-defective yeast strain and when cytosol from this mutant is used in an in vitro assay. In addition, ERAD is limited in vitro in the presence of the proteasome inhibitors, 3,4-dichloroisocoumarin and lactac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
314
0
4

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 424 publications
(331 citation statements)
references
References 43 publications
9
314
0
4
Order By: Relevance
“…This result was unexpected given that A1PiZ is an ERAD substrate in both yeast (McCracken and Kruse, 1993;Werner et al, 1996;Brodsky et al, 1999) and human . Because vacuole morphology is largely unperturbed in vps30 yeast (Raymond et al, 1992), these data suggest that the A1PiZ degradation defect does not arise from gross ultrastructural perturbations.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…This result was unexpected given that A1PiZ is an ERAD substrate in both yeast (McCracken and Kruse, 1993;Werner et al, 1996;Brodsky et al, 1999) and human . Because vacuole morphology is largely unperturbed in vps30 yeast (Raymond et al, 1992), these data suggest that the A1PiZ degradation defect does not arise from gross ultrastructural perturbations.…”
Section: Discussionmentioning
confidence: 50%
“…The classical form of A1Pi deficiency results from the Z variant (A1PiZ) that contains a K342E substitution (Bathurst et al, 1984;Crystal, 1990). A1PiZ homozygous individuals can develop emphysema via a loss-of-function mechanism because the altered conformation of A1PiZ results in its recognition and degradation by ERAD (Wu et al, 1994;Werner et al, 1996;Teckman et al, 2001). A subset of homozygous individuals (12-15%) also experience liver disease (Sveger, 1988) via a gain-offunction mechanism because A1PiZ accumulates and aggregates within the ER of hepatocytes (Lomas et al, 1992, Lomas andMahadeva, 2002; reviewed in Perlmutter, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Although retrograde translocation from the ER to the cytoplasm has been demonstrated for some luminal substrates of the proteosome, very limited evidence exists for retrograde translocation of ␣1ATZ. Werner et al 17 detected ␣1ATZ in the cytosolic fraction of yeast when the proteosome was inhibited, but it was only a small fraction of the total ␣1ATZ in the ER, and there has been no other evidence for retrotranslocation. This may mean that other mechanisms provide for transport from the ER to the cytoplasm such as proteosomemediated extraction through the ER membrane, as has been demonstrated for model ER degradation substrates.…”
Section: Degradation Of Mutant ␣1atz In the Ermentioning
confidence: 99%
“…Studies in many systems have indicated that the proteosomal system is involved. [17][18][19][20][21] This involvement appears to include both the classical ubiquitin-dependent proteosomal mechanism as well as a ubiquitin-independent proteosomal mechanism. 19 However, exactly how ␣1ATZ on the luminal side of the ER membrane is accessed by the proteosome from the cytoplasm is not clear.…”
Section: Degradation Of Mutant ␣1atz In the Ermentioning
confidence: 99%
“…We discovered that the mutated protein was exported from the ER vesicles into the cytosolic fraction, an event that required ER lumenal chaperones (9). We and others subsequently found that the degradation of these ''retro-translocated'' ER proteins was mediated by the cytosolic proteasome, a 26S multicatalytic protease that had been previously found to trigger the destruction of misfolded cytoplasmic proteins (10,11). We termed this process ERassociated degradation (ERAD).…”
Section: Protein Quality Control In the Ermentioning
confidence: 99%